1990
DOI: 10.1080/09540129008257746
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, drugs and AIDS-related risks: Results from a prospective study

Abstract: This paper examines the relationship between AIDS-related risks amongst a cohort of young adults and alcohol, tobacco and illicit drug use. Data were elicited by standardized interview and self completed questionnaires from a non-random study group of 350 males and 428 females. Only a minority of respondents reported always using condoms during sexual activity. Over half the study group reported having had only one sexual partner in the past year. Levels of condom use were not significantly associated with gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 5 publications
2
26
1
2
Order By: Relevance
“…Entretanto, tanto o beber pesado quanto o beber moderado, antes ou durante o ato sexual, foram associados à prática de sexo sem preservativo, múltiplos parceiros, parceiro casual, prática sexual com profissionais do sexo e uso de drogas injetáveis (Bagnall et al, 1990;HalpernFelsher et al, 1996;Leigh et al, 1994;Madhivanan et al, 2005).…”
Section: Consumo De áLcool E Comportamento Sexual De Riscounclassified
“…Entretanto, tanto o beber pesado quanto o beber moderado, antes ou durante o ato sexual, foram associados à prática de sexo sem preservativo, múltiplos parceiros, parceiro casual, prática sexual com profissionais do sexo e uso de drogas injetáveis (Bagnall et al, 1990;HalpernFelsher et al, 1996;Leigh et al, 1994;Madhivanan et al, 2005).…”
Section: Consumo De áLcool E Comportamento Sexual De Riscounclassified
“…Detox clients were 3.7 times more likely than MM clients to engage in high-risk sexual behavior (95% CI 1.6-8.1, P = 0.002), an effect that remained constant even when controlling for the younger mean age of Detox clients. This may reflect the role of the Detox as a substance abuse treatment entry point, in which clients are actively using drugs or alcohol and therefore are more likely to be engaging in risky sexual behavior (Ross et al, 1999;Aktan et al, 2001;Bagnall et al, 1990;Ericksen and Trocki, 1992;Fitterling et al, 1993;Flom et al, 2001;Morrill et al, 2001;Purcell et al, 2001;Scheidt and Windle, 1995;Somlai et al, 2000;Zenilman et al, 1994). It also may reflect the lower motivation to enter meaningful treatment, and thus reflect repeated and long-standing patterns of risky behavior associated with chronic drug use.…”
Section: Substance Abuse and High-risk Sexual Behaviormentioning
confidence: 99%
“…Several studies have demonstrated that people with heavy alcohol use tend to engage in riskier behaviors, such as sex with multiple partners, unprotected vaginal and anal intercourse, and injection drug use (Bagnall et al, 1990;Fenaughty and Fisher, 1998;Halpern-Felsher et al, 1996). In Asia, drinking alcohol is often associated with the highrisk behavior of engaging in sex, usually unprotected, with a commercial sex worker (Fordham, 1995;Gibney et al, 2003;Kim et al, 1998;MacQueen et al, 1996;Poudel et al, 2004;Wee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%